Wealth creation and disease burden: Evidence from Nigeria based on a Bayesian-VAR approach - Milena Lopreite; Zhen Zhu (PLoS ONE, 2025)
Does wealth creation reduce disease burden for developing countries? In this paper a Bayesian-VAR (B-VAR) model is built to investigate the causal relationships between disease burden, wealth creation, life expectancy at birth and population growth over the period from 2006 to 2018 in Nigeria, a developing country with significant disease burden. Specifically, the use of the impulse response functions and the forecast variance decomposition functions reveal that wealth creation has the greatest impact on disease burden in Nigeria. Our results are consistent with different measurements of wealth creation, including trade in services, personal remittance received, and ease of doing business. We have also found a pronounced response of disease burden to life expectancy at birth and to population growth. Our results suggest that, in Nigeria, policies targeted at wealth creation, with a proper wealth redistribution, are strongly recommended to reduce disease burden and increase life expectancy at birth.